Using of modern patterns of intraoperative fluid resuscitation in orthopedic oncology - Lyzogub, Kseniia; Kursov, Sergii; Lyzogub, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to study the changes in central hemodynamics, transport and oxygen consumption in patients who underwent planned surgical interventions in oncologic orthopedics using different regimes of intraoperative fluid supply. Methods: study included 70 patients aged 18 to 77 years who underwent surgery under combined anesthesia — spinal injection of bupivacaine and intravenous propofol-fentanyl anesthesia. Patients of the 1st group (n = 35) were provided with a restrictive mode of intraoperative fluid administration, 2nd (n = 35) — targeted liquid therapy with careful monitoring of cardiac output and target support of the stroke index at a level of more than 35 ml/ m2, mean arterial pressure not less than 90 mm Hg. art. In patients of the 1st group, cardiac preload was often modeled with norepinephrine, the 2nd — it was maintained by short-term infusions of a solution of hydroxyethyl starch. Results: it was established that when the fluid support is limited (group 1), cardiac output, vascular tone, and oxygen uptake are significantly reduced. More than 40 % of patients (with 100 % of elderly and senile patients) needed to introduce noradrenaline to stabilize central hemodynamics. Patients of the 2nd group had significantly better cardiac output, vascular tone, oxygen consumption, did not need noradrenaline. Conclusions: purposeful liquid therapy contributes to the stabilization of central hemodynamics indices, provides better oxygen metabolism, which is especially important for elderly and senile patients in patients who are routinely operated in orthopedic oncology for malignant pathology of lower limb bones under combined anesthesia.